2011
DOI: 10.1007/s00535-011-0499-2
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytapheresis for steroid-dependent ulcerative colitis in clinical practice: results of a nationwide Spanish registry

Abstract: In clinical practice, apheresis allows long-term steroid-free clinical remission in up to one third of steroid-dependent UC patients, even in those with prior failure of thiopurines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 31 publications
1
13
0
3
Order By: Relevance
“…GMA is aimed at reducing the elevated and activated leucocytes known to be sources of inflammatory cytokines 1,321. In most hitherto studies, the efficacy outcomes have been promising.…”
Section: Introductionmentioning
confidence: 99%
“…GMA is aimed at reducing the elevated and activated leucocytes known to be sources of inflammatory cytokines 1,321. In most hitherto studies, the efficacy outcomes have been promising.…”
Section: Introductionmentioning
confidence: 99%
“…El primero es la obtención de remisión completa inicial, siendo el periodo libre de recidiva significativamente mayor en este caso que en caso de lograr solo una respuesta parcial inicial. Es preciso considerar en este sentido que una cierta proporción de pacientes que inicialmente solo presentan una respuesta parcial, alcanzan la remisión tardía, a los 3-6 meses, sin otras medidas asociadas 30,35 . En los distintos estudios la eficacia de la aféresis se ha evaluado entre una semana y un mes tras la última sesión; pero la aféresis actúa de forma lenta al menos con las pautas convencionales de una sesión semanal y diversos mecanismos involucrados en ella, como la disminución en la expresión de los receptores de chemocinas o el incremento de linfocitos CD4+, se han confirmado varias semanas después de aplicar el tratamiento.…”
Section: Duración De La Respuesta Resultados a Largo Plazounclassified
“…Este es el caso del reciente registro nacional (SiMAC) donde se incluyeron 142 pacientes con CU dependiente de corticoides tratados con aféresis leucocitaria, mostrando una tasa de mejoría inicial del 68%, con un 37% de remisión clínica completa al mes de la última sesión. En el seguimiento a largo plazo el 41% del total de la cohorte tratada a los 6 meses y el 36% al año mantuvieron la remisión clínica libre de corticoides 35 . El GETECCU ha promovido un estudio controlado multicéntrico internacional, actualmente en desarrollo, que ayudará a evaluar el papel de la aféresis en este escenario.…”
Section: Colitis Ulcerosa Dependiente De Corticoidesunclassified
See 1 more Smart Citation
“…Previous studies exploring the clinical efficacy of GMA in active UC have shown controversial results . After the observation of absence of clinical benefit in the initial clinical trial, further evidence from another open‐label clinical trial and real‐world studies have shown that this technique may be specially effective in steroid‐dependent UC …”
Section: Discussionmentioning
confidence: 99%